Environmental occurrence of the antibiotics and their ecotoxicological prediction through the use of the Gecotoxic ® computational program - Argota Pérez, George (2020)
The exposure of antibiotics in water is an environmental concern where comprehensive methodologies are needed to signal early the probability of risk. The objective of the study was to describe the environmental occurrence of antibiotics and its predictive ecotoxicological through the Gecotoxic® computer program. By non-probabilistic sampling for convenience, a scientific review article was selected assessing, the number of antibiotics and only ciprofloxacin; oxytetracycline, sulfamethoxazole, trimethoprim and erythromycin (out of 39) were represented on the four continents assessed: Africa, America, Asia-Pacific and Europe. Other studies considered the correlational limitation between bioassays, tax source characterization data, physical-chemical parameters and / or associated environmental matrix analyses. It was concluded that the ecotoxicology of antibiotics is predictable through the Gecotoxic® computational program, as it considers the medium toxicity bioassay test that was analyzed in the selected article.